Mild SARS-CoV-2 Infections and Neutralizing Antibody Titers - Bonfante, Francesco; Costenaro, Paola; Cantarutti, Anna; Di Chiara, Costanza; Bortolami, Alessio; Petrara, Maria Raffaella; Carmona, Francesco; Pagliari, Matteo; Cosma, Chiara; Cozzani, Sandra; Mazzetto, Eva; Di Salvo, Giovanni; et al. (Pediatrics (Evanston), 2021)
BACKGROUND Recent evidence suggests that neutralizing antibodies (nAbs) to severe acute respiratory syndrome coronavirus 2 may persist over time; however, knowledge regarding pediatric subjects is limited. METHODS A single-center, prospective observational study was conducted on 57 family clusters of coronavirus disease 2019, including children of neonatal and pediatric age attending the University Hospital of Padua (Italy). For each patient, blood samples were collected for both the quantification of nAbs through a plaque reduction neutralizing test and the detection of antinucleocapsid-spike protein immunoglobulin G and/or immunoglobulin M. RESULTS We analyzed 283 blood samples collected from 152 confirmed coronavirus disease 2019 cases (82 parents and 70 children or older siblings of median age of 8 years, interquartile range: 4–13), presenting asymptomatic or with mildly symptomatic disease. Despite the decrease of immunoglobulin G over time, nAbs were found to persist up to 7 to 8 months in children, whereas adults recorded a modest declining trend. Interestingly, children aged <6 years, and, in particular, those aged <3 years, developed higher long-lasting levels of nAbs compared with older siblings and/or adults. CONCLUSIONS Mild and asymptomatic severe acute respiratory syndrome coronavirus 2 infections in family clusters elicited higher nAbs among children.